Prevalence of Parasitic Infections in Buffaloes in and around Ludhiana District, Punjab, India: A Preliminary Study - Singh, Nirbhay Kumar; Singh, Harkirat; ., Jyoti; Haque, Manjurul; Rath, S S (Journal of Buffalo Science, 2012)
A total of 598 buffaloes were sampled for both coprological (210) and haematological (388) investigations at the Large Animal Clinics, GADVASU, Ludhiana, Punjab, India. Coprological examination revealed that the overall prevalence of gastrointestinal (GI) parasitic infections was 23.33% (49/210). Among the revealed parasites, amphistomes, Fasciola spp., Eimeria spp., Balantidium coli and strongyles were in 4.29, 3.33, 0.95, 2.86 and 15.71% of the examined buffaloes. Except coccidiosis, there was no significant variation of GI infections in relation to sex. Eimeria spp. was significantly higher in males. The present work emphasized that strongyles were the most prevalent gastrointestinal parasites found during coprological examination of buffaloes in Punjab, India. Examination of Giemsa-stained peripheral blood smears exhibited that 4.9% (19/388) of buffaloes were infected with haemoparasites comprising Theileria annulata (2.32%), Trypanosoma evansi (1.8%), Babesia bigemina (0.26%) and Anaplasma marginale (0.77%). Mixed infection appeared in one (0.26%) animal. Trypanosomosis was predominant in elder animals with no infection recorded in males.